Kekosongan Norma dan Rekonstruksi Perlindungan Hukum bagi Korban Kekerasan Seksual dalam Relasi Pacaran Pasca Undang-Undang Nomor 12 Tahun 2022 - Mulyadi Mulyadi; R Eriska Ginalita Dwi (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Sexual violence in dating relationships is increasing alongside the development of non-marital intimate relationships, yet it is frequently regarded as a private matter. Law Number 12 of 2022 recognises power imbalance as an element of sexual violence but does not explicitly regulate dating relationships as a protected context, creating legal vulnerabilities for victims. This study aims to analyse victim protection arrangements for sexual violence in dating relationships under the Sexual Violence Law and identify normative gaps that limit effective protection. This normative legal research employs statutory and conceptual approaches. Primary legal materials include the Sexual Violence Law, Domestic Violence Law, Witness and Victim Protection Law, and related regulations, while secondary materials consist of scholarly articles, books, and institutional reports collected through literature review. Data were analysed qualitatively-normatively through grammatical and systematic interpretation, supported by comparative analysis between relevant legal frameworks. The findings reveal that the Sexual Violence Law provides a legal basis through the recognition of power imbalance and victims’ rights to handling, protection, and recovery. However, protection remains general and lacks operational mechanisms. Eight normative gaps were identified, including the absence of a dating-relationship definition, unclear indicators of power imbalance, lack of immediate protection mechanisms independent of marital status, and limited trauma-informed and digital protection standards. This study recommends normative strengthening through implementing regulations that ensure legal certainty, effective protection, and sustainable access to justice for victims. The novelty lies in reconstructing dating-relationship-specific protection based on power-relations theory, victimology, and access to justice.